A humanized mouse model to study mast cells mediated cutaneous adverse drug reactions. Issue 5 (10th January 2020) - Mencarelli, Andrea; Gunawan, Merry; Yong, Kylie Su Mei; Bist, Pradeep; Tan, Wilson Wei Sheng; Tan, Sue Yee; Liu, Min; Huang, Edwin Kunxiang; Fan, Yong; Chan, Jerry Kok Yen; Choi, Hae Woong; Abraham, Soman N.; et al.
Abstract: Recently a G-protein-coupled receptor, MAS Related GPR Family Member X2 (MRGPRX2), was identified as a specific receptor on human mast cells responsible for IgE independent adverse drug reactions (ADR). Although a murine homologue, Mrgprb2, has been identified for this receptor, its affinity for many ADR-causing drugs is poor making it difficult to undertake in vivo studies to examine mechanisms of ADR and to develop therapeutic strategies. Here, we have created humanized mice capable of generating MRGPRX2-expressing human MCs allowing for the study of MRGPRX2 MCs-mediated ADR in vitro as well as in vivo. Humanized mice were generated by hydrodynamic-injection of plasmids expressing human GM-CSF and IL-3 into NOD- scid IL2R-γ −/− strain of mice that had been transplanted with human hematopoietic stem cells. These GM/IL-3 humice expressed high numbers of tissue human MCs but the MRGPRX2 receptor expressed in MCs were limited to few body sites including the skin. Importantly, large numbers of MRGPRX2-expressing human MCs could be cultured from the bone marrow of GM/IL-3 humice revealing these mice to be an important source of human MCs for in vitro studies of MRGPRX2-related MCs activities. When GM/IL-3 humice were exposed to known ADR causing contrast agents (meglumine and gadobutrol), the humice were found to experience anaphylaxis analogous to the clinical situation. Thus, GM/IL-3 humice represent a valuable model for investigating in vivo interactions of ADR-causing drugs and human MCs and their sequelae, and these mice are also a source of human MRGPRX2-expressing MCs for in vitro studies.